How well do light-use efficiency models capture large-scale drought impacts on vegetation productivity compared with data-driven estimates?. (February 2023) - Lv, Yiming; Liu, Jinxiu; He, Wei; Zhou, Yanlian; Tu Nguyen, Ngoc; Bi, Wenjun; Wei, Xiaonan; Chen, Hui
Highlights: Five LUE models were evaluated against data-driven GPP products and ancillary data. Data-driven models are able to reasonably well represent GPP dynamics at site levels. The simulated GPP by LUE models reasonably responded to droughts at regional scales. Considerable differences existed in the amplitude and phase of GPP seasonal anomalies. LUE models consistently exhibited a likely misrepresentation of drought legacy effects. Abstract: Remote sensing driven light-use efficiency (LUE) models are an important tool for estimating vegetation gross primary productivity (GPP) and assessing climate change impacts on the terrestrial carbon cycle, but their capacity in representing drought impact on GPP over large-scales is not fully explored. Here, we evaluated a suite of LUE models, i.e., VPM, TL-LUE, CASA, EC-LUE and MuSyQ, against two data-driven flux products (GOSIF-GPP and FluxSat), with the aids of environmental variables and eddy covariance flux measurements over North America. The two data-driven GPP products were firstly validated against with eddy covariance flux measurements, suggesting that they are able to reasonably indicate drought impacts at site scales. They were then used as a reference to evaluate these LUE models for indicating the drought impacts in 2011 and 2012 over North America at regional scales. In general, the simulated GPP by these models reasonably responded to droughts, but showed considerable differences in the seasonal anomalies for both amplitude and phase. Especially, these models consistently showed a clearly earlier trough (about 1 ∼ 2 months) of flux reduction than those in data-driven models over both entire drought-impacted regions and individual ecosystems (mostly pronounced for grasslands), indicating a likely misrepresentation of drought legacy effects, which needs to be considered in developing new-generation LUE models. Among the grass-dominated drought areas, TL-LUE and VPM performed best in indicating the impacts of the 2011 and 2012 droughts on regional GPP, respectively, while EC-LUE showed a significant underestimation of the impacts in both events, which may be attributed to the different representations of water stress factors in models. This study could provide some useful hints toward improving LUE models in characterizing drought impacts on regional GPP.